2007
DOI: 10.1002/adfm.200700012
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Hydrogels that Promote Osteogenic Human Mesenchymal Stem Cell Differentiation Through Stimulation and Sequestering of Bone Morphogenic Protein 2

Abstract: The extracellular environment controls many cellular activities thereby linking external material cues to internal cell function. By better understanding these processes, synthetic extracellular material niches can be tailored to present cells with highly regulated physical and/or chemical cues that promote or suppress selected cell functions. Here, poly(ethylene glycol) (PEG) hydrogels were functionalized with fluvastatin-releasing grafts and growth factor binding heparin domains to enable the dynamic exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 41 publications
1
98
0
Order By: Relevance
“…Thus, we can promote specific cell-material interactions-eg, through particular integrins [1,3]. Other cell functions such as differentiation can be modulated by incorporating releasable drug delivery mechanisms in PEG hydrogels [3,6] to further promote specific cellular effects we posit to be important toward allograft revitalization.…”
Section: Proposed Programmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, we can promote specific cell-material interactions-eg, through particular integrins [1,3]. Other cell functions such as differentiation can be modulated by incorporating releasable drug delivery mechanisms in PEG hydrogels [3,6] to further promote specific cellular effects we posit to be important toward allograft revitalization.…”
Section: Proposed Programmentioning
confidence: 99%
“…Based on careful design and thorough in vitro established cohort of degradable hydrogels capable of controlling numerous MSC functions, we expect our newly developed periosteum-mimetics to enhance the healing of allograft tissue in vivo [1][2][3][4][5][6][7]. Loss of osteocytes during allograft devitalization may contribute to an overall decrease in graft resorption and remodeling as compared with autograft controls [45].…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogel constructs functionalized with heparin and fluvastin have also been proposed for bone repair. Benoit (Benoit et al, 2007) showed that the developed scaffolds were able to promote osteogenic differentiation of human MSCs. Similarly, Edlund et al (2008) reported that BMP-2 loaded in heparin functionalized polymers improved adhesion and proliferation of murine MSCs.…”
Section: Hydrogels In Acellular Strategies For Disc Regenerationmentioning
confidence: 99%